Perlindungan Terhadap Anak Korban Eksploitasi Seksual dalam Perspektif Yuridis-Normatif dan Psikologis (Studi Kasus Wilayah Hukum Polres Lampung Timur). - Permatasari, Ermanita (al-'adalah, 2016)
Abstract: Analysing the Protection of Children Sexual Exploitation Victim from Yuridical-Normative and Psychological Perspectives: A Case in the Police Resort of East Lampung Region. This study analyzes the handling of cases of children sexual exploitation in the Police Resort of East Lampung Region. Child sexual exploitation is a type of sexual abuse in which children are sexually exploited for money, power or status. The cases of exploitation of children, known as CSEC, are .increasingly prevalent lately and pose a concern from many parties. This is because the CSEC problem is not only a legal issue, but also involves other aspects, religion, psychology, sociology and Medic. This study finds out that the handling of cases of CSEC in the Police Resort East Lampung Region have been running optimally, starting from the registration of the complaint process, examination of the victim, guarding the anonymity of victims, relief, until the process of rehabilitation. The pattern of handling of such cases is realy in accordance with the principles of Islamic law.Abstrak: Perlindungan Terhadap Anak Korban Eksploitasi Seksual dalam Perspektif Yuridis-Normatif dan Psikologis (Studi Kasus Wilayah Hukum Polres Lampung Timur). Penelitian ini menganalisis penanganan kasus eksploitasi seksual terhadap anak di wilayah hukum Polres Lampung Timur. Kasus eksploitasi terhadap anak, yang dikenal dengan sebutan CSEC, akhir-akhir ini kian marak dan menimbulkan keprihatinan banyak pihak. Hal ini dikarenakan masalah CSEC tidak hanya merupakan isu hukum, tetapi juga involves other aspects, such as religion, Psychology, sociology and Medis. Penelitian ini menemukan bahwa penanganan kasus CSEC di Polres Lampung Timur telah berjalan secara optimal mulai dari tahap penerimaan pengaduan, pemeriksaan korban, penjagaan kerahasiaan identitas korban, pemberian bantuan, hingga proses rehabilitasi korban. Pola penanganan kasus yang demikian bukan saja sesuai dengan Standard Operating Procedures tetapi juga sesuai dengan prinsip-prinsip dalam hukum Islam.